THE USE OF THE INQUIRY LEARNING MODEL IN IMPROVING STUDENTS' CRITICAL THINKING ABILITY IN IPS LESSONS CLASS VIII SMP IT MIFTAHUL FALAH - Karinah Karinah; Sri Winarsih (Panca Sakti Bekasi : Jurnal Pendidikan dan Bisnis, 2022)
This study was aimed at finding out that the use of inquiry learning learning models was able to improve students' critical thinking skills in social studies subjects in class VIII at SMP IT Miftahul Falah. This is because the students at SMP IT Miftahul Falah still have low critical thinking skills, this can be seen from the learning activities where students tend to be less active and only receive information from the teacher without trying to dare to express their own ideas or thoughts. Apart from that, low critical thinking skills are also indicated by low scores obtained from the results of daily tests held in the reflection section of the learning activity stage. The design in this study was a pre-experimental design using a one group pretest-posttest design, which only used one experimental class without a control or comparison class. In this design there is a pretest before being given treatment and a posttest after being given treatment. The results of the pretest test in table 2 in general are still in the low category, namely as many as 25 students the average score on the pretest is 2.76 and this is classified as very low category, but after the application of the inquiry learning model the average score of students on the test results posttest which is 7. Thus there is an increase in student learning outcomes that is equal to 37% of the total pretest and posttest scores. The results of the N-Gain Test on students' critical thinking skills are 0.58 in the medium category after the application of the inquiry learning model. Therefore, it can be concluded that the use of the inquiry learning model in the social studies learning process in class VIII can affect students' critical thinking skills